Effects of collective tactical variables and predictors on the probability of scoring in elite netball - Hodder, R. W.; Hopkins, W. G.; Ball, K. A.; Serpiello, F. R. (International Journal of Performance Analysis in Sport, 2023)
In netball, understanding the group behaviours and constraints that can influence the probability of scoring can provide information that impacts the outcome of a match. The aim of this study was to model the effects of collective tactical variables and contextual predictors on scoring probability in elite netball. A local positioning system provided player positions of one team throughout seven national-level netball matches. The positions were analysed to provide mean, variability (standard deviation) and irregularity (normalised approximate entropy) for each attack and defence possession (470 and 423, respectively) for the team and positional subgroups (forwards, midcourts and defenders) for 10 collective tactical variables. The effects of collective tactical variables on the probability of scoring were estimated with a logistic-regression version of the generalised linear mixed model, with adjustment for predictor variables; possession duration, score difference, match time, ladder-points difference, and match number. The home team and opposition team displayed a greater probability of scoring when they were able to maintain possession for longer periods of time, extremely short possessions were associated with decreased scoring probability. Lateral dispersion negatively affected the probability of scoring for both teams, indicating it is more favourable to maintain positioning and ball movement in the middle of the court.